Inflammatory Bacteriome and Oral Squamous Cell Carcinoma - Perera, M; Al-Hebshi, N N; Perera, I; Ipe, D; Ulett, G C; Speicher, D J; Chen, T; Johnson, N W (Journal of dental research, 2018)
Results from microbiome studies on oral cancer have been inconsistent, probably because they focused on compositional analysis, which does not account for functional redundancy among oral bacteria. Based on functional prediction, a recent study revealed enrichment of inflammatory bacterial attributes in oral squamous cell carcinoma (OSCC). Given the high relevance of this finding to carcinogenesis, we aimed here to corroborate them in a case-control study involving 25 OSCC cases and 27 fibroepithelial polyp (FEP) controls from Sri Lanka. DNA extracted from fresh biopsies was sequenced for the V1 to V3 region with Illumina's 2 × 300-bp chemistry. High-quality nonchimeric merged reads were classified to the species level with a prioritized BLASTN-based algorithm. Downstream compositional analysis was performed with QIIME (Quantitative Insights into Microbial Ecology) and linear discriminant analysis effect size, while PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) was utilized for bacteriome functional prediction. The OSCC tissues tended to have lower species richness and diversity. Genera Capnocytophaga, Pseudomonas, and Atopobium were overrepresented in OSCC, while Lautropia, Staphylococcus, and Propionibacterium were the most abundant in FEP. At the species level, Campylobacter concisus, Prevotella salivae, Prevotella loeschii, and Fusobacterium oral taxon 204 were enriched in OSCC, while Streptococcus mitis, Streptococcus oral taxon 070, Lautropia mirabilis, and Rothia dentocariosa among others were more abundant in FEP. Functionally, proinflammatory bacterial attributes, including lipopolysaccharide biosynthesis and peptidases, were enriched in the OSCC tissues. Thus, while the results in terms of species composition significantly differed from the original study, they were consistent at the functional level, substantiating evidence for the inflammatory nature of the bacteriome associated with OSCC.